2019
DOI: 10.1111/jerd.12512
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant tissue management after immediate implant placement using a customized healing abutment

Abstract: Objective The unavoidable extraction of teeth in the esthetic area can be overcome through different treatment modalities. Recently, immediate implants appeared as a minimally invasive approach to resolving these cases; however, immediate implant loading is not always possible or indicated. In these cases, an innovative approach through customized healing abutments could be used to preserve the soft tissue contour, eliminating the need for reopening surgery and the use of provisional restorations to condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 36 publications
2
28
0
13
Order By: Relevance
“…The use of customized healing abutments, when an implant is inserted in a fresh extraction socket, has been described as a beneficial solution that permits to personalize the peri-implant tissues architecture. [15][16][17][18]24,25 This study demonstrated that, in the first month of treatment, the use of customized healing abutments is favorable in preventing linear and volumetric peri-implant tissue loss (Figure 5). CA group exhibited approximately half less the volumetric dimensional variation than CM group (À12.98 ± 14.53 mm 3 and À25.20 ± 17.44 mm 3 ; p = 0.049, respectively).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The use of customized healing abutments, when an implant is inserted in a fresh extraction socket, has been described as a beneficial solution that permits to personalize the peri-implant tissues architecture. [15][16][17][18]24,25 This study demonstrated that, in the first month of treatment, the use of customized healing abutments is favorable in preventing linear and volumetric peri-implant tissue loss (Figure 5). CA group exhibited approximately half less the volumetric dimensional variation than CM group (À12.98 ± 14.53 mm 3 and À25.20 ± 17.44 mm 3 ; p = 0.049, respectively).…”
Section: Discussionmentioning
confidence: 83%
“…22,23 On the other hand, the use of customized healing abutments in IIP is a growing subject but almost limited to description of techniques and case reports in terms of scientific evidence. [15][16][17][18]24,25 Recently, an RCT from Perez and colleagues, 26 comparing customized healing abutments and standard healing abutments at IIP sites, showed favorable results in terms of papilla presence and marginal bone loss at the sites treated with customized abutments, when compared with the standard healing abutments sites. In our investigation, all the experimental sites were carefully selected and classified as type 1 extraction sockets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall treatment planning, including periodontal, surgical, 22 and prosthodontic therapy, 23–25 in addition to quality control throughout the manufacturing process, 26 contributes to the success of the treatment. The patient was satisfied with the titanium‐reinforced PMMA provisional full‐arch ISFDP due to improved function and aesthetics (Fig 5H).…”
Section: Discussionmentioning
confidence: 99%
“…To cope with this anatomical consideration several authors have proposed using a customized abutment to seal the large molar socket after the immediate implant placement, and maintaining the original outline of soft tissues 21‐26 . For instance, the Sealing Socket Abutment (SSA) technique introduced by Finelle et al 2017 uses an individualized chairside‐fabricated abutment following tooth extraction to seal the surgical area and to protect the bone grafting material from the oral cavity exposure as well.…”
Section: Introductionmentioning
confidence: 99%